Large-Scale Integrated Photonics for Energy-Efficient AI Hardware - Tossoun, Bassem; Liang, Di; Xiao, Xian; Cheung, Stanley; Singaraju, Prerana; Srinivasan, Sudharsanan; Descos, Antoine; Hu, Yingtao; Baek, Jongseo; London, Yanir; Yuan, Yuan; Peng, Yiwei; et al. (Digest of the LEOS Summer Topical Meetings, 2024)
The convergence of deep learning models and the availability of large datasets has spurred significant interest in developing new hardware that can run AI algorithms more energy-efficiently. At Hewlett Packard Labs, we've developed an energy-efficient silicon photonics platform, a foundational technology for next-generation AI hardware.